Artificial Intelligence in the Discourse of Hadith Science - Damayanti, Amelia; Wulandari, Susi (Proceedings of International Conference on Muslim Society and Thought, 2024)
The current existence of Artificial Intelligence (AI) shows that the convenience of technology is increasingly showing progress. Easily accessed by all levels, anywhere and anytime, quickly and concisely, is a breakthrough brought by AI to support various human needs. However, something that is fast and concise will make users complacent. Without re-checking the answers given by the artificial system. In fact, artificial intelligence will not be free from errors, so it has an impact on academics and one of them is in the discourse on hadith science, it is not enough to rely on the system but needs further research as is the tradition carried out by scholars in hadith science. The aim of this research is to find out how AI becomes an opportunity and challenge for academics discussing hadith science and provide solutions to these cases. By using a qualitative research method based on library research, the author will explore the extent of the positive and negative impacts of the emergence of AI and how to take a stance in facing technological advances, especially AI in the hadith science discourse. The author hopes that this research will make academics increase their sense of wisdom towards technological progress and not abandon the rules that have been established by muhaddithin.